Treatment of canine pancreatitis using membrane-free stem cell extract and its anti-inflammatory effect - Choi, Yongsoo; Lee, Miae; Kim, BoMyoung; Kim, Youngsil (Frontiers in Veterinary Science, 2025)
Canine pancreatitis can lead to the digestion of nearby organs, and if untreated, it can develop into peritonitis. Widely used treatment as of now for acute pancreatitis (AP), however, largely depends on supportive treatment such as fluid therapy, antibiotics, and sufficient nutrient intake. Membrane-free stem cell extract (MF-STEM) is a protein mixture and other bioactive molecules derived from human adipose stem cells. MF-STEM is known for its anti-inflammatory and regenerative effects. This study was a vehicle-controlled clinical study. One hundred and forty-five canine pancreatitis patients with pancreatitis participated in this study with owners’ consent. Following the owners’ consent, 63 dogs received MF-STEM cell therapy with conventional therapy, and 82 dogs received conventional therapy. All participants had their cPL and CRP measured to evaluate their clinical progression. At the time of discharge, the survival rate in the MF-STEM cell therapy group survived (survival 92% and mortality 8%) more than the control group (survival 46% and mortality 54%). The authors suppose that MF-STEM cell increases survival of pancreatitis patients by modulating inflammatory cytokines. There were no side effects observed, such as allergic reactions and hypersensitivity reactions.